THE CHURCH MUSICIANS AND THEIR IMPORTANT ROLES IN WORSHIP - Dante Oblimar (Jurnal Theologia Forum STFT Surya Nusantara, 2019)
Many musicians find themselves engaged in different musical activities of their respective church affiliations all throughout the year. In the Philippines, Malaysia, Indonesia, Singapore, and Thailand, where I had the privilege of working with the Seventh-day Adventist Churches, musicians are tasked to handle leadership function as elected church officers to take charge of the musical needs of the church. Their main function includes assigning singers, accompanists, instrumentalists, and song leaders for each weekly services such as the Midweek Prayer Meeting, Vespers, Sabbath School program, Hour of Worship, and sometimes even for the afternoon service efor the youth. As a practice, a music committee is formed which may include the membership of the elected music leader, associates, church pastor, and the elder for music. The committee usually appoints other musicians who may be requested to provide music for the church such as a choir director for adult, youth, and for children. They are also requested to prepare programs for church special celebrations such as thanksgiving, year-end gatherings, and others. Outreach activities where musical parts are needed keep the musicians busy not to mention their involvement in other services such as funerals, hospital or sick visitations, and others. Keywords: Worship and Music